(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1 - Introduzione - 2. Il quadro pluralistico dell’ebraismo diasporico e delle sue organizzazioni - 3. Peculiarità dell’organizzazione dell’ebraismo italiano - 4. Pluralismo interno e tensioni nel contesto unitario delle Comunità - 5. Le origini storiche del peculiare assetto organizzativo dell’ebraismo italiano: l’assenza del movimento riformato in Italia e la normativa statualistica del 1930-31 - 6. La struttura unitaria e l’adesione delle Comunità all’ortodossia nello Statuto e nell’Intesa - 7. Conclusioni: la necessaria conciliazione tra pluralismo e unitarietà tra le varie anime dell’ebraismo italiano. The Union of Italian Jewish Communities between adherence to Orthodox Judaism and representation of all Jew in Italy: Is the constitutional Agreement of 1987 with the Italian State still adequate? ABSTRACT: Relations between Italian Judaism and the Italian State are governed legally by the Agreement (“Intesa”) concluded in 1987 pursuant to Article 8 of the Italian Constitution, enforced by Law No. 101 of 1989.The organization of the Italian Jewish communities and their central “Union” is governed by the By-Laws (“Statuto”) adopted by them at that time, which reflect the Intesa. In conformity also with the tradition of Italian Judaism local communities take care of all Jewish activities, religious, social or educational, and the Unione officially represents all Jews and Jewish groups. Since 1987 however, there has been an explosion of various Jewish groups and denominations in Italy, from the Lubavitch to Reformed groups, which organize themselves autonomously. These groups considers themselves part of Italian Judaism and recognize more or less the central role of the local communities and Unione. However they increasingly ask a say in the latter management.. The issue discussed in the paper is whether the unitary structure of Italian Judaism, as enshrined in Intesa and recognized by Italian public authorities, is still adequate to cope with this evolution, and whether a plurality of independent Jewish organizations, separately recognized by Italian authorities would be compatible with Article 8 of the Constitution and preferable in practice.